Reversed Economics and Inhumanity of Development Assistance in Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Purpose The purpose of this paper is to assess the aid-development nexus in 52 African countries using updated data (1996-2010) and a new indicator of human development(adjusted for inequality). Design/methodology/approach The estimation technique used is a Two-Stage-Least Squares Instrumental Variable approach. Instruments include: income-levels, legal-origins and religious-dominations. The first-step consists of justifying the choice of the estimation technique with a Hausman-test for endogeneity. In the second-step, we verify that the instrumental variables are exogenous to the endogenous components of explaining variables(aid dynamic channels) conditional on other covariates(control variables). In the third-step, the strength and validity of the instruments are examined with the Cragg-Donald and Sargan overidentifying restrictions tests respectively. Robustness checks are ensured by: (1) the use of alternative aid indicators; (2) estimation under restricted and unrestricted hypotheses ; and (3) adoption of two interchangeable sets of instruments. Findings The findings broadly indicate that development assistance is detrimental to GDP growth, GDP per capita growth and inequality adjusted human development. Given concerns on the achievement of the MDGs, the relevance of these results point to the deficiency of foreign aid as a sustainable cure to poverty in Africa. Social implications It is a momentous epoque to solve the second tragedy of foreign aid; it is high time economists and policy makers start rethinking the models and theories on which foreign aid is based. In the meantime, it is up to people who care about the poor to hold aid agencies accountable for piecemeal results. Originality/value These findings are based on data collected after pioneering works on the aid-development nexus. Usage of the inequality adjusted human development index first published in 2010, corrects past works of the bunch of criticisms inherent in the first index.
Keywords: B20; F35; F50; O10; O55; 330; Foreign Aid; Political Economy; Development; Africa